2018
DOI: 10.3390/biom8040099
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Evaluation of Anti-Obesity Activity, Acute Toxicity, and Subacute Toxicity of Probiotic Dark Tea

Abstract: Probiotic dark tea (PDT) is a novel kind of dark tea produced by fresh albino tea leaves and fermented with specific probiotics. Our study demonstrates that PDT can ameliorate high-fat diet-induced overweight and lipid metabolic disorders and shows no acute or subacute toxicity in Sprague-Dawley (SD) rats. Daily intragastric administration of 5% PDT infusion for 14 days caused no obvious effect on general physiological features and behaviors of rats. Oral administration of 1%, 2%, and 3% of PDT infusion for si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…The antiobesity consequence of probiotic dark tea was assessed in high-fat diet fed Sprague-Dawley (SD) rats. Probiotic dark tea lowered the body weight rise, serum triglycerol levels and serum total glycerol levels in extraordinary fat diet SD rats 86 . It is also shown that obesity is linked with increased Firmicutes, while the concentration of Bacteroidetes is reduced in obese patients 87 .…”
Section: Anti-obesity Propertiesmentioning
confidence: 91%
“…The antiobesity consequence of probiotic dark tea was assessed in high-fat diet fed Sprague-Dawley (SD) rats. Probiotic dark tea lowered the body weight rise, serum triglycerol levels and serum total glycerol levels in extraordinary fat diet SD rats 86 . It is also shown that obesity is linked with increased Firmicutes, while the concentration of Bacteroidetes is reduced in obese patients 87 .…”
Section: Anti-obesity Propertiesmentioning
confidence: 91%
“…In the past decades, many studies have shown that G. pentaphyllum has a variety of biological activities, such as anticancer, anti-tumor, anti-gastric ulcer, anti-inflammation, cardio-protection and strengthening the immune system [6]. Although the G. pentaphyllum herb contains the active ingredients saponin, amino acids, flavonoids, essential oils and polysaccharides, polysaccharides may have greater bioavailability than others because they are water soluble and can be easily soaked out into a tea infusion [7,8]. Many evidences have shown that the polysaccharide components obtained from G. pentaphyllum herbs exhibited significant bioactivities, including antioxidant, anti-cancer, anti-tumor, anti-aging, immunomodulatory and anti-exercise fatigue effects [5].…”
Section: Introductionmentioning
confidence: 99%
“…The Biomolecules Editorial Office has been made aware that the published paper [1] was previously published in chinese in China Tea Processing by the same authors [2]. In order to preserve academic integrity, the title paper [1] will be marked as retracted. We apologize to the readership of Biomolecules for any inconvenience caused.…”
mentioning
confidence: 99%
“…We apologize to the readership of Biomolecules for any inconvenience caused. The decision to retract has been made in cooperation with the authors of the article [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation